Newly qualified nurses' perceptions of working at mental health facilities: A qualitative study. Issue 5 (31st May 2019) - Mabala, Jaftaline; van der Wath, Annatjie; Moagi, Miriam
Accessible summary: What is already known about the topic?: Newly qualified nurses often feel overwhelmed by the challenges of the work environment and struggle to transition into healthcare work environments. Nurses require opportunities during the transition period to develop both competence and confidence in their ability to practise independently. What the paper adds to existing knowledge?: Newly qualified mental health nurses experience fear during their adaptation period, especially when they perceive mental healthcare users as dangerous and the working environment as risky, with little concern for their safety. Nurses new to the mental health environment learn from accepting responsibility, taking on challenges and making adjustments, in order to develop confidence as mental healthcare professionals. What are the implications for practice?: Nursing management should ensure a safe and supportive mental healthcare environment. The potential for and consequences of negative stereotyping of patients among mental health nurses should be acknowledged and addressed as it may hinder the smooth adaptation of newly qualified nurses. Although stressful experiences can help mental health nurses to develop confidence and skills to manage future demanding situations, newly qualified nurses need to be given appropriate support and debriefing to ensure challenging situations do not "go the wrong way" and decrease confidence levels. Abstract: Introduction: Much has been written about the experiences of newly qualified nurses in their first year of employment, yet not much has been heard from the perspectives of newly qualified nurses working in mental health facilities. Aim: To explore and describe the adaptation process of newly qualified nurses working in public mental health facilities in South Africa. Method: Following a qualitative descriptive design, 11 newly qualified nurses in their first 6–18 months of employment were purposively selected from three public mental health facilities in South Africa. Data collected through unstructured individual interviews were thematically analysed. Results: Four themes emerged from the analysis: fear related to the mental healthcare environment; self‐doubt upon meeting the expectations of the inter‐professional team; ways to adjust to the challenges; and confidence as mental healthcare professionals. Discussion: During the adaptation process newly qualified nurses working in mental health facilities need support to overcome their initial fears and develop self‐confidence in both managerial and therapeutic realms. Implications for practice: Management of mental healthcare facilities needs to be cognisant of the importance of creating a supportive and safe environment that discourages negative stereotyping of patients and fosters newly qualified nurses' adaptation.